2001
DOI: 10.1002/1521-4141(200104)31:4<1055::aid-immu1055>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

IL-12-induced reversal of human Th2 cells is accompanied by full restoration of IL-12 responsiveness and loss of GATA-3 expression

Abstract: IL‐12 is a potent inducer of IFN‐γ production and drives the development of Th1 cells. Human polarized Th2 cells do not express the signaling β2‐subunit of the IL‐12R and, therefore, do not signal in response to IL‐12. The question was raised as to what extent the loss of the IL‐12Rβ2 chain in Th2 cells has bearing on the stability of the human Th2 phenotype. In the present report, we show that restimulation of human fully polarized Th2 cells in the presence of IL‐12 primes for a shift towards Th0/Th1 phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 40 publications
2
42
0
Order By: Relevance
“…IL12 has direct antitumor activity by inducing IFNg and inhibiting angiogenesis and IL12 should protect the transduced CTLs from the Th2 environment, increasing their ability to persist, proliferate and function within the tumor environment. 38 Indeed we demonstrated that transgenic expression of IL12 in CTL not only increases Th1 and decreases Th2 cytokine production but also creates resistance to the antiproliferative and anticytotoxic effects of TGFb, which is secreted by HD tumors. 4 TGFb and IL12 act through different specific signaling pathways, Targeting IL12 to HD by EBV-specific CTL H-J Wagner et al but have antagonistic effects on the expression of T-bet, a transcription factor crucial for Th1 development and differentiation.…”
Section: Discussionmentioning
confidence: 86%
“…IL12 has direct antitumor activity by inducing IFNg and inhibiting angiogenesis and IL12 should protect the transduced CTLs from the Th2 environment, increasing their ability to persist, proliferate and function within the tumor environment. 38 Indeed we demonstrated that transgenic expression of IL12 in CTL not only increases Th1 and decreases Th2 cytokine production but also creates resistance to the antiproliferative and anticytotoxic effects of TGFb, which is secreted by HD tumors. 4 TGFb and IL12 act through different specific signaling pathways, Targeting IL12 to HD by EBV-specific CTL H-J Wagner et al but have antagonistic effects on the expression of T-bet, a transcription factor crucial for Th1 development and differentiation.…”
Section: Discussionmentioning
confidence: 86%
“…The basal GATA-3 expression seen in naive Th cells is inhibited in Th1-polarizing conditions (9), and it has also been hypothesized that suppression of GATA-3 expression in short-term Th2-polarized cells can occur in Th1-polarizing conditions (5,32). The model shows that a decrease in the parameter combination k G ͞ below a threshold (Fig.…”
Section: Gata-3 Can Attain Two Stable Expression Levelsmentioning
confidence: 93%
“…The shift of Th2 cells into a Th1 phenotype can also occur when fully Th2 polarized cells are restimulated with IL-12, which leads to elevated levels of T-bet and decreased GATA-3 expression (Smits et al, 2001), indicating a direct role for IL-12 in the activation of T-bet. Consequently, it has been suggested that inhibition of GATA-3, rather than positive regulation of the IFN-γ gene is the main function of T-bet (Usui et al, 2006).…”
Section: The T-bet / Gata-3 Balancementioning
confidence: 99%